Ascendant theory of power, colonial contract and national literature. The porteñas’ lower classes and the narrative of the port of Valparaíso as political and cultural dissidence - Rojas Castro, Braulio Claudio (2020)
In this article, a genealogy is made of the configuration of "national literature" as opposed to "regional literatures" and "marginal literatures". This effort is based on a genealogy of the formation of the lower classes in Chile as an expression of the emancipatory political power that is mobilized in modernity from the deployment of the ascendant theory of power and Hispanic municipalism. Important is to highlight the processes of political and cultural organization of the lower classes expressed in writings which are marginalized from the national literary canon in the formation of the Republic of Chile and of Chilean sociability from the perspective of the social history and the theory of the colonial contract. Finally, this analyze on marginal literature will be fundamental to understand the literary representation of a port geopoetics and of the lower class from a position of dissident minority in Valparaiso.